2012
DOI: 10.5114/wo.2012.31770
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer in patients under the age of 40 years

Abstract: Aim of the studyIn the paper clinical cases of individuals diagnosed with lung cancer below the age of 40 years have been analyzed.Material and methodsThe analysis included: sex, age, clinical symptoms found before and at the moment of diagnosis, character of changes visible in radiological imaging, time that passed from the first symptoms to reporting to a doctor and to establishing a diagnosis, type of diagnostic method used in establishing the final diagnosis, histopathologic type of cancer, degree of cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 5 publications
3
25
0
Order By: Relevance
“…FLC patients tended to have more AD histology, other cancer history, distant organ metastasis and stage IV cases, the latter two are indicator of increased cancer aggressiveness. Studies on young lung cancer patients also supported high AD ratio, prevalence of female and diagnosed in advanced stages (25, 26, 28, 29). Other interesting results included: the age curve of our FLC and sporadic males separated clearly, while age curve of our FLC and sporadic females almost overlapped with each other (Figures 4F,H).…”
Section: Discussionmentioning
confidence: 74%
“…FLC patients tended to have more AD histology, other cancer history, distant organ metastasis and stage IV cases, the latter two are indicator of increased cancer aggressiveness. Studies on young lung cancer patients also supported high AD ratio, prevalence of female and diagnosed in advanced stages (25, 26, 28, 29). Other interesting results included: the age curve of our FLC and sporadic males separated clearly, while age curve of our FLC and sporadic females almost overlapped with each other (Figures 4F,H).…”
Section: Discussionmentioning
confidence: 74%
“…Lung cancer, in both sexes combined, was the most commonly diagnosed cancer (2.1 million new cases, 11.6% of the total cancer cases) and the leading cause of cancer death (1.8 million deaths, 18.4% of the total cancer deaths) in 2018 [1]. Although lung cancer occurs in adult patients of all ages, it predominates among people over 50 years old, most often at the age of 60-75 years [2]. Unsurprisingly, comorbidities are common in patients with lung cancer, including diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…When a young male patient, in the third decade of life, presents with a lung mass and large pleural and pericardial effusion, amongst the most common pathologies initially considered are lymphoma, sarcoma, testicular carcinoma, and primary lung carcinoma. A review of the literature revealed about 2-5% of all lung cancer cases involve patients with an average age of 34 years, equal rates in men and women, and adenocarcinoma is the most common type of lung cancer [1,2]. A careful review of the past medical history, initial presentation, and physical exam findings are important to determine the initial workup and treatment.…”
Section: Introductionmentioning
confidence: 99%